Biaya Pendidikan Tinggi bagi Mahasiswa dengan Keterbatasan Ekonomi, Seberapa Besar Dampaknya? - Nopriani Rara'; Trivena Trivena (Jurnal Keguruan dan Ilmu Pendidikan, 2022)
Education has a very important role in everyone's life, especially in view of the increasing national development, because in national development it requires quality people in every aspect. The aim of this study is to further examine the impact of the cost of education on people with economic limitations in pursuing higher education. The method used is descriptive, with the result being a descriptive form. The data collection technique used a literature study technique. The results of the literature review state that the cost of higher education is very important to ensure the implementation of education. However, given the high public and private costs of higher education in Indonesia, economic constraints are also a barrier to students' willingness to pursue higher education. This results in the community being less able to make many impacts, so it impacts on awareness raising, street children and crime. Therefore, it needs government attention, one of which is to provide opportunities for people who do not have access to the world of education, so that both rich and poor can have equal rights in education. Of course, by providing equal education for all people, it will make a great contribution to the national development of nation and state.